Epileptic Seizure Provoked by Bone Metastasis of Chronic Lymphoid Leukemia and Merkel Cell Carcinoma - András Folyovich; Angéla Majoros; Tamás Jarecsny; Gitta Pánczél; Zsuzsanna Pápai; Gábor Rudas; Lajos Kozák; Gábor Barna; Katalin A. Béres-Molnár; Károly Vadasdi; Gabriella Liszkay; Eszter Horváth; et al. (Case Reports in Medicine)
Background. Merkel cell carcinoma (MCC) is a rare primary neuroendocrine cutaneous tumor, rarely metastasizing to the brain. Chronic lymphoid leukemia (CLL) is a disease predisposing to MCC. According to previous reports, headache and focal neurological deficits suggest disease progression to the brain. We present a patient with MCC whose seizure was not elicited by a cerebral metastasis, but by bone metastases compressing the brain. Case Presentation. A 62-year-old female patient had a history of CLL. A lesion with the appearance of an atheroma was removed from the right upper arm. Histology confirmed the diagnosis of MCC. She was admitted to the neurology department with her first GM seizure. The cranial MRI/MRA showed bone metastases in the right parietal and both frontal areas, compressing the brain. Flow cytometry of CSF did not reveal metastasis of MCC. Conclusions. The case history of the patient was unique even among the rare cases of MCC with neurological involvement. The seizure was not elicited by a cerebral metastasis, but by bone metastases compressing the brain. In addition to patient history, clinical presentation and radiological findings enabled a suspected diagnosis of skull metastasis of MCC compressing the brain, causing symptomatic epileptic seizures.